Activation of the Renin-Angiotensin System in Anti-glomerular Basement Membrane Antibody-Induced Glomerulonephritis - HAYASHI, Kazumi; YAYAMA, Katsutoshi; SUZUKI, Yoshio; NAGAMATSU, Tadashi; OKAMOTO, Hiroshi; TAKANO, Masaoki; MATSUI, Takashi (Biological & pharmaceutical bulletin, 1995)
Activity of the reain-angiotensin system in the nephrotic syndrome was investigated in rats with acute nephritis induced by anti-glomerular basement membrane (GBM) antibody. Injection of anti-GBM antibody resulted in a transient 2-fold elevation of both plasma reain and angiotensinogen with a peak at 12 h. Angiotensinogen mRNA levels in the liver also rapidly and transiently increased 4-fold at 3 h. The manifestation of acute nephritis, indicated by proteinuria, hypoalbuminemia, hypercholesterolemia and an increase in serum creatinine, following injection of anti-GBM antibody, was inhibited by a single administration of the selective angiotensin II type 1 receptor antagonist TCV-116 (1 mg/kg, p.o.) 2 h before an injection with the antibody, but not by successive administration of this drug for 1 week from 3 d after the injection of antibody. These results suggested that the enhanced generation of angiotensin II by elevated levels of both renin and its substrate in the early phase of anti-GBM nephritis promotes the evolution of acute nephritis via angiotensin II type 1 receptor.